Utilization of essential neonatal health care and associated factors among underprivileged ethnic groups in Bardiya district. - Sanjel,Keshab (2018)
SUMMARY: Globally, neonatal death accounts 44 percent of under-five deaths in 2015. Nepal is one of the developing countries with the high number of neonatal death. Unequal distribution of the neonatal mortality rate has been reported among different regions, religious, and ethnic groups. There are higher rates of neonatal mortality among poor socio-economic groups, Muslims and Dalits, as well as people living in remote areas. Recommendations about evidence based neoonatal care practices may conflict with local beliefs and practices. So, it is important to understand the existing neonatal care utilization and associated factors in order to take interventions so as to decrease neonatal death. The general objective of the study was to assess the utilization pattern of essential neonatal health care and associated factors among mothers from underprivileged ethnic groups in Bardiya district. Variables studied were grouped under demographic, socio-economic and health services related factors. Association of these variables with neonatal care utilization was analysed. The study was cross sectional mixed method, in which qualitative data was embedded within quantitative design. A total of 362 underprivileged women having a live baby within past twelve months preceding the study were interviewed using structured questionnaire. Ten key informants were also enrolled for key informant interview. The dependent variable, essential neonatal care utilization was determined by using Principle component Analysis (PCA). The composite index of the neonatal care was created and dichotomized for further analysis. Descriptive analysis as well as analysis of association was performed. Chi square test was performed to identify the existence of significant association between essential neonatal care utilization and selected factors. Logistic regression model was used to determine the factors associated with essential neonatal care utilization. Audio recording, transcription and thematic content analysis were done for the qualitative data. Overall status of neonatal care utilization in this study was found as 58.6 percent. Factors such as birth order (AOR 2.059, 95% CI: 1.129-3.752), ethnicity (AOR 2.277, 95% CI 1.327-3.909), religion (AOR 2.368, 95% CI 1.027-5.456), perceived quality of services (AOR 2.661, 95% CI 1.6134.391), awareness on immediate essential newborn cares (AOR 2.223, 95% CI 1.2773.870) and awareness on newborn danger signs (AOR 1.199, 95% CI 0.638-2.256) were significantly associated with neonatal care utilization. This study provided important findings that disparities in health care utilization exist within underprivileged ethinic groups as evidenced by difference in neonatal care utilization between Tharu and non- Tharu underprivileged ethnic groups, and Hindu and other religions. Further, health service factors were also contributing towards the poor utilization of neonatal cares. Implementing targeted interventions addressing all the components of the minimum neonatal care package along the continuum of care can possibly increase the essential neonatal care utilization. Addressing disparities in the distribution of maternal and neonatal care services, targeting more resources and care services to disadvantaged ethnic minority women, raising their level of awareness on essential neonatal care and emphasizing quality of maternal and neonatal care services could increase the essential neonatal care utilization among underprivileged ethnic groups of Bardiya district.